Investigating English Teachers’ Awareness of the Teaching Methods That Should be used in Teaching the Sunrise Series in Zakho City, Duhok-Iraq - Murad, Ivan H. (Humanities Journal of University of Zakho, 2017)
This is a small-scale study that aims to investigate Zakho city English teachers’ awareness of the teaching methods that should be used in teaching Sunrise Series. The current study collected both qualitative and quantitative data utilising different data collection methods. The participants of the study were 38 teachers from Zakho city teaching in different levels (primary, secondary, and high school). These 38 teachers were chosen to respond to a questionnaire especially designed to achieve the objectives of the study. Nine of these participants were chosen to be interviewed. Each three were chosen to represent a level of education mentioned above. This study also employed different data analysis methods so as to obtain valid results. Results revealed that the majority of the teachers at Zakho city are aware of the English teaching methods but do not know which ones should be used in teaching the Sunrise curriculum. It was also revealed that they are using classical methods in teaching a curriculum which is especially designed to be taught according to the CLT approach. Finally, this study also found that the majority of the teachers need improvement in their teaching practices, particularly in teaching the Sunrise Series.